VARIATIONS IN ELECTROPHYSICAL PARAMETERS ESTIMATED FROM ELECTROMAGNETIC MONITORING DATA AS AN INDICATOR OF FAULT ACTIVITY - A. E. Shalaginov; N. N. Nevedrova; I. O. Shaparenko (Геодинамика и тектонофизика)
In the regions of high seismic activity, investigations of fault zones are of paramount importance as such zones can generate seismicity. A top task in the regional studies is determining the rates of activity from the data obtained by geoelectrical methods, especially considering the data on the faults covered by sediments. From a practical standpoint, the results of these studies are important for seismic zoning and forecasting of natural and anthropogenic geodynamic phenomena that may potentially occur in the populated areas and zones allocated for construction of industrial and civil objects, pipelines, roads, bridges, etc. Seismic activity in Gorny Altai is regularly monitored after the destructive 2003 Chuya earthquake (M=7.3) by the non-stationary electromagnetic sounding with galvanic and inductive sources of three modifications. From the long-term measurements that started in 2007 and continue in the present, electrical resistivity and electrical anisotropy are determined. Our study aimed to estimate the variations of these electrophysical parameters in the zone influenced by the fault, consider the intensity of the variations in comparison with seismicity indicators, and attempt at determining the degree of activity of the faults. Based on the results of our research, we propose a technique for measuring and interpreting the data sets obtained by a complex of non-stationary sounding modifications. The technique ensures a more precise evaluation of the electrophysical parameters. It is concluded that the electric anisotropy coefficient can be effectively used to characterize the current seismicity, and its maximum variations, being observed in the zone influenced by the fault, are characteristic of the fault activity. The use of two electrophysical parameters enhances the informativeness of the study.